2018
DOI: 10.3390/s18020490
|View full text |Cite
|
Sign up to set email alerts
|

A Strain-Based Method to Detect Tires’ Loss of Grip and Estimate Lateral Friction Coefficient from Experimental Data by Fuzzy Logic for Intelligent Tire Development

Abstract: Abstract:Tires are a key sub-system of vehicles that have a big responsibility for comfort, fuel consumption and traffic safety. However, current tires are just passive rubber elements which do not contribute actively to improve the driving experience or vehicle safety. The lack of information from the tire during driving gives cause for developing an intelligent tire. Therefore, the aim of the intelligent tire is to monitor tire working conditions in real-time, providing useful information to other systems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
2
28
0
1
Order By: Relevance
“…While such a method can be applied to detect friction potential indicators, different levels of pavement roughness still cause undesirable vibration and a negative influence on results. As an alternative to the accelerometer, the strain gauges have been mounted in the inner liner surface of the tyre to characterise the grip [14]. The experimental research showed strong straining parameters relation with tyre lateral force but for limited grip.…”
Section: Introductionmentioning
confidence: 99%
“…While such a method can be applied to detect friction potential indicators, different levels of pavement roughness still cause undesirable vibration and a negative influence on results. As an alternative to the accelerometer, the strain gauges have been mounted in the inner liner surface of the tyre to characterise the grip [14]. The experimental research showed strong straining parameters relation with tyre lateral force but for limited grip.…”
Section: Introductionmentioning
confidence: 99%
“…The discrete form representations of constraints are straight-forward to define, with the exception of the dynamics constraint (6), which involves first and second order derivatives of r(s) with respect to the arclength s. We use finite differences to approximate r (s),…”
Section: Discretization Of R (S) and R (S)mentioning
confidence: 99%
“…Although constantly pursuing high speeds is not the goal of autonomous driving, varying weather conditions may have impact on the road quality in such a way as to dramatically reduce the friction coefficients and in consequence the maximum safe velocity limits for vehicles [4]. Thanks to the rapid development of mature sensing, perception and scene understanding system relying on computer vision and machine learning techniques for autonomous driving, high level information such as weather conditions, road surface categories, together with vehicle state information, can be delivered from on-board perception systems to road friction estimators [5,6]. The environment-dependent, varying friction coefficient becomes available to speed or motion planners online, which can be used to generate safety-guaranteed speed profiles.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the results were apparently independent of the position of the strain gauge. Some other researches have successfully developed intelligent tires based on strain gauge measurements, achieving advanced systems to estimate tire characteristics [16,17,18,19,20]. Matsuzaki and Todoroki [1] investigated the relationship between variation in strain on the inner surface of pneumatic tires and tire mechanical parameters by carrying out finite element analysis and simulating the strain sensor signal when a tire rotates.…”
Section: Introductionmentioning
confidence: 99%